Elements of geography - Finch, Vernor C. (McGraw-Hill book company, 1942)
This book introduce the physical elements of geography, the elements of weathe and climate, climatic types and their distribution, processes concerned with origin of landforms. The cultural elements of geography features resulting from man's use of land.